Inadequação de consumo, antropometria e estilo de vida de universitárias da área de saúde - Souza, Luciana Bronzi de [UNESP]; Malta, Maíra Barreto [UNESP]; Donato, Patricia Moreira; Corrente, José Eduardo [UNESP]; Carvalhaes, Maria Antonieta Barros Leite [UNESP]; Papini, Silvia Justina [UNESP] (My University, 2012)
Objective – To assessing the food intake, anthropometry and lifestyle of female university students in the health area. Method – One hundred and twelve students who attend the 2nd year of some courses in the health area at UNESP-Botucatu were evaluated in 2007. Data on: physical activity, alcohol intake, smoking habits, anthropometry (BMI, waist circumference and bioimpedance) and dietary intake were collected through three days food records. Results – Regarding the classification of students according to Body Mass Index (BMI), it was observed that 12.5% were overweight, 4.5% were underweight and the others showed normal weight. Waist circumference was below average students of predicted risk and the mean percentage of body fat within the limits considered acceptable. Smoking and alcohol consumption was less prevalent, however, there was a high level of physical inactivity. We have observed a statistically significant relationship between physical activity and body fat percentage (p = 0.0182). The average energy consumption was similar to the one expected from the group (p = 0.184) as well as the distribution of macronutrients. We found high percentages of inadequate intake of vitamin E (97.7%), folate (94.4%), zinc (38%) and thiamine (30%). Conclusion – The obtained results are worrying, since there is an imbalance in the intake of micronutrients for most of this population, and high rate of inactivity, especially because it is a population composed by students of the health area, who supposedly, should enhance the healthy eating and being multipliers of the information in society.

Objetivo – Avaliar o consumo alimentar, antropometria e estilo de vida de universitárias da área de saúde. Método – Foram avaliadas 112 alunas do 2º ano de cursos da área de saúde da UNESP de Botucatu no ano de 2007. Foram coletados dados sobre: prática de atividade física, ingestão de álcool, uso de tabaco, antropometria (peso, estatura, circunferência abdominal), realizada a análise da composição corporal por bioimpedância elétrica (BIA) e de consumo alimentar através de registro alimentar de três dias. Resultados – Quanto à classificação das alunas segundo Índice de Massa Corporal (IMC) foi observado que 12,5% apresentaram sobrepeso, 4,5% baixo peso e as demais apresentaram eutrofia. A circunferência abdominal média das alunas estava abaixo do valor considerado de risco e o valor médio da porcentagem de gordura corporal dentro do limite considerado aceitável. O tabagismo e a ingestão de bebida alcoólica foram pouco prevalentes, entretanto, observou-se alto nível de sedentarismo. Foi observada uma relação estatisticamente significativa entre a prática de atividade física e a porcentagem de gordura corporal (p=0,0182). A média de energia consumida foi semelhante à preconizada para o grupo (p=0,184) bem como a distribuição de macronutrientes. Foram encontradas elevadas porcentagens de inadequação de consumo de vitamina E (97,7%), folato (94,4%), zinco (38%) e tiamina (30%). Conclusão – Os resultados são preocupantes, pois apontam o desequilíbrio no consumo de micronutrientes, além de elevado índice de sedentarismo, ainda mais por se tratar de uma população composta por universitárias da área de saúde, que supostamente, deveriam valorizar hábitos de vida saudáveis e serem multiplicadores dessas informações na sociedade.
Inadequate food intake, anthropometry and lifestyle of college healthcare students
Keywords: Food habits; Macronutrients; Micronutrients; Anthropometry; Motor activity; Hábitos alimentares; Macronutrientes; Micronutrientes; Antropometria; Atividade motora